1977
DOI: 10.1113/jphysiol.1977.sp011855
|View full text |Cite
|
Sign up to set email alerts
|

Sodium currents in mammalian muscle

Abstract: SUMMARY1. A method is described which allows the approximate computation of membrane current from measurements with three electrodes in the midregion of a muscle fibre.2. Measurements of inward sodium current in frog muscle are compared with the results of previous clamping studies to test the validity of the new method.3. Sodium current in rat muscle (extensor digitorum longus) is in general similar to sodium current in frog muscle. Two differences in detail have been found between sodium current in rat and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
76
1

Year Published

1979
1979
1990
1990

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(94 citation statements)
references
References 23 publications
17
76
1
Order By: Relevance
“…Most of the results with intact fibers were obtained with the three-microelectrode method applied to the end of a fiber (Adrian et al, 1970). The only exception is the work of Hollingworth and Marshall (1981), who used the three-microelectrode method applied to the middle of a fiber (Adrian and Marshall, 1977). Movement in intact fibers was reduced by making the external solutions hyperosmotic with sucrose.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the results with intact fibers were obtained with the three-microelectrode method applied to the end of a fiber (Adrian et al, 1970). The only exception is the work of Hollingworth and Marshall (1981), who used the three-microelectrode method applied to the middle of a fiber (Adrian and Marshall, 1977). Movement in intact fibers was reduced by making the external solutions hyperosmotic with sucrose.…”
Section: Discussionmentioning
confidence: 99%
“…However, it would be a serious obstacle to analysis of the kinetics of slow inward current activation. Such analysis might be carried out more easily using the second difference method of Adrian & Marshall (1977), which measures current density in the vicinity of the nearer voltage electrode.…”
Section: Discussionmentioning
confidence: 99%
“…Recent experiments have shown that the membrane currents of mammalian muscle under voltage clamp are qualitatively similar to those of frog muscle (Pappone, 1977;Adrian & Marshall, 1977;Duval & Leoty, 1978). This paper presents a full account of the conductance changes during depolarization in cut pieces from fasttwitch rat skeletal muscle fibres studied using the vaseline-gap clamp.…”
Section: Introductionmentioning
confidence: 99%